THE INFLUENCE OF GRIT TOWARDS WORK ENGAGEMENT AND THE MODERATING ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT - Yudiarti, Andina; Putranta, M. Parnawa (Jurnal Aplikasi Manajemen, 2022)
Grit has been found before as a non-cognitive predictor beyond talent and intelligence, which drives a person to exert the best potential. This study investigates the influence of grit on work engagement, which contains perseverance of effort and consistency of interest. It also investigated the role of perceived organizational support in moderating this influence. The research analysis unit comprised 252 health workers and Medical Laboratory Technicians, with a minimum working period of three years, who were active as employees working in medical laboratories in various institutions, the Special Region of Yogyakarta and Central Java. Data is processed using SEM-PLS with SmartPLS 3.2 software. The study's results revealed a positive influence on the perseverance of efforts, the consistency of interest, and perceived organizational support on work engagement. In its role as moderating, perceived organizational support is found to weaken the influence of perseverance of effort on work engagement and strengthen the influence of consistency of interest on work engagement. These findings are expected to provide direction for organizations to increase support for employee self-development.